Inside Back Cover: Nanoparticles weaponized with built‐in functions for imaging‐guided cancer therapy (View 2/2020). Issue 2 (26th June 2020) - Jing, Lihong; Yang, Chen; Zhang, Peisen; Zeng, Jianfeng; Li, Zhen; Gao, Mingyuan
Abstract : In article number 19, Mingyuan Gao and co‐workers demonstrate that imaging‐guided cancer therapy (IGCT) holds remarkable promise for revolutionizing precision cancer theranostics, while it strongly relies on advanced theranostic agents that are largely constructed on top of nanomaterials. Nanoparticles with built‐in functions, particularly those who can naturally combine novel imaging with versatile phototherapies by converting near‐infrared (NIR) light into heat or radicals, are comprehensively summarized herein.